Influence of Particular Design Parameters of Radial Guide Vane Cascades on Their Hydraulic Performance at Variable Speed Operated Francis Turbines - Filip Stojkovski; Zoran Markov (Energija, Ekonomija, Ekologija)
The design of radial blade cascades, with the intent to become turbine guide vanes, lies in the basis of satisfying turbine runner needs for a particular turbine design point of interest. For conventional turbine operation, the hydrodynamic parameters in the pre-runner space can be relatively easily estimated. For variable speed turbine operation at the constant head, these parameters change in a way that cannot be easily predicted using conventional techniques. In this paper, the guide vanes, as crucial turbine sub-system which needs to perform efficient runner flow feeding for these operating ranges, are numerically tested in various geometrical shapes and configurations, to observe the cascades behaviour, in a way of estimating which cascade configuration satisfies certain hydrodynamic and efficiency considerations of the operating points of interest. The criteria which the guide vanes need to meet are based on hydrodynamic parameters and expansion of the turbine operating range.